1995
DOI: 10.1002/j.2050-0416.1995.tb00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ethanol in Beer by Direct Injection Gas Chromatography: A Comparison of Six Identical Systems

Abstract: Six identical gas chromatographic (GC) systems from the same manufacturer were evaluated for the determination of ethanol in beers. Each system was assessed for detector linearity and drift using standard ethanol solutions. Repeatability (rss) of each machine, repeatability (rss) of the GC method and reproducibility (Rss) of the method over a range of ethanol concentrations (1-11% V/V) was determined using commercial beers. All six instruments were linear over the ethanol range 0-12% V/V and were in good agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…For ethanol determination, various instrumental methods such as gas chromatography (Clarkson et al 1995), liquid chromatography coupled with absorbance or fluorescence detection (Vitrac et al 2002), spectrophotometry (Lázaro et al 1986;Segundo and Rangel 2002) or enzymatic test-kits have been reported. However, these methods are laborious, expensive, time-consuming, and complex to perform.…”
Section: Introductionmentioning
confidence: 99%
“…For ethanol determination, various instrumental methods such as gas chromatography (Clarkson et al 1995), liquid chromatography coupled with absorbance or fluorescence detection (Vitrac et al 2002), spectrophotometry (Lázaro et al 1986;Segundo and Rangel 2002) or enzymatic test-kits have been reported. However, these methods are laborious, expensive, time-consuming, and complex to perform.…”
Section: Introductionmentioning
confidence: 99%